Developing STEM literacy with young learners - Mairead Holden (IUL Research, 2020)
This paper presents a vignette, accompanied by reflections, which describe the author’s recent experience using a constructionist pedagogy, Bridge 21, as part of an exploratory 21st century STEM learning experience with a group of young learners in an Irish primary school setting. The aim of the learning experience was to develop pupil participants’ STEM Literacy, as well as enabling pupils to develop the 21st century skills of critical thinking, creativity and communication. Combining the Bridge 21 Model with playful pedagogy, pupils were facilitated to explore the concept of gravity through engaging in play-based activities, with pupils capturing their learning using Seesaw, an e-portfolio tool. Implications are derived for educators who may be interested in using a 21st century constructionist approach as part of their STEM practice